Sistem Pendukung Keputusan Penilaian Hasil Belajar Mahasiswa Dengan Metode Topsis Di STMIK Pelita Nusantara Medan - Murni Marbun; Bosker Sinaga (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
This research is the manufacture of Decision Support System based on computer for the assessment of student learning outcomes in STMIK Pelita Nusantara Medan with TOPSIS method. Assessment of learning outcomes by lecturer should be consistent with the ongoing assessment of education standards to monitor progress and improvement processes in various forms of tests or examinations. Assessment of learning outcomes by educational unit aims to assess the achievement of graduate competency standards for all courses. Continuous education assessment requires a system that can help lectures to convey to students more timely and provide more objective assessments. The required system is Computer Based Decision Support System, which is a computer-based system designed to improve the effectiveness of decision makers in solving problems. Implementation of decision support systems built using Visual Basic programming language 2010 and the database is MySQL. The result of this research is the application of Decision Support System by applying TOPSIS method that gives the result of the final value of the student, which can help the lecturer in determining the learning result of students STMIK Pelita Nusantara Medan. Implementation of this system is to display the names of students with the final value in the form of letters A, B, C, D or E. Key Words : Decision Support System, TOPSIS, the value of learning outcomes